In vivo antioxidant activity of Ethanolic extract from root of Smilax zeylanica on Aluminium Chloride Induced oxidative stress in Wistar rats - Senthil, B. Sabari; Kalaichelvan, V.K.; Kottai Muthu, A. (Journal of Drug Delivery and Therapeutics, 2018)
Objective: The objective of the present study was to investigate the Evaluation of In vivo antioxidant activity of Ethanolic extract of root of Smilax zeylanica(EESZ) on Aluminium Chloride Induced apoptosis suppressing oxidative stress in Wistar rats. Materials and Methods: The ethanolic extract from the roots of S. china by hot continuous percolation method. The rats were divided into 5 groups and each group consists of 6 animals. Rats were treated with EESC for 150 and 300 mg/ kg of body weight and piracetam, 0.5 mg/ kg of body weight for 14 successive days after inducing oxidative stress with aluminium chloride (100 mg/ kg of body weight) for 60 days. The lipid peroxidation level (TBARS) and antioxidant activities like Superoxide dismutase (SOD), Catalase (CAT) and reduced Glutathione (GSH) were estimated in rats. Results: AlCl3 induced rats showed increased the TBARS and decreased the antioxidant enzymes like Superoxide dismutase (SOD), Catalase (CAT) and reduced Glutathione (GSH) when compared with the control group. The EESZ at higher dose 300 mg/ kg of body weight animals were significantly (P < 0.001) reduced the TBARS and increased the anti oxidant enzymes Superoxide dismutase (SOD), Catalase (CAT) and reduced Glutathione (GSH) when compared with the AlCl3 treated group Conclusion: Findings of the present study revealed that Ethanolic extract from roots of Smilax zeylanica may be used as a significant source of natural antioxidant, which might be helpful in preventing the progress of various oxidative stresses. Keywords: S. zeylanica, antioxidant, ethanolic extract, TBARS, rats.